AMBIGUITAS FORMAT ACARA REALITY SHOW PADA PROGRAM RUMAH UYA - Suhada, Siti (Journal of Sustainable Transformation, 2025)
Reality shows are among the most popular television programs in Indonesian society. A reality show is a program created based on actual events that happen to an individual or a group without fabrication and is based on facts. One of the programs that once became a ‘favorite’ among Indonesian audiences was Rumah Uya. The AC Nielsen survey agency released rating results for this program, showing that it had one of the highest viewership percentages. Rumah Uya is a show that presents the life problems of individuals to Uya, the host, who then provides solutions to the issues faced. This research employed a qualitative descriptive research method. The data was collected by observing the episode and interviewing the talent who was involved in this show. The result showed that this program labels itself as a reality show. However, its classification becomes ambiguous when examined through the content segmentation, which does not align with the fundamental characteristics of a true reality show. Based on the facts and data, this program is a dramatic reality as it undergoes a casting process and is scripted by the production team.